2021
DOI: 10.1111/bjd.20440
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in eicosanoid‐related biosynthesis enzymes associated with acute urticaria/angioedema induced by nonsteroidal anti‐inflammatory drug hypersensitivity

Abstract: Background Nonsteroidal anti-inflammatory drugs (NSAIDs) are the main triggers of drug hypersensitivity, with NSAID-induced acute urticaria/angioedema (NIUA) the most frequent phenotype. NSAID hypersensitivity is caused by cyclooxygenase 1 inhibition, which leads to an imbalance in prostaglandin (PG) and cysteinyl leukotriene (CysLT) synthesis. As only susceptible individuals develop NSAID hypersensitivity, genetic factors are believed to be involved; however, no study has assessed the overall genetic variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…The analysis of associations with atherosclerosis measurements revealed that PTGS1 rs10306194, tagging the distal region of the gene coding for COX1, was the most relevant SNP, as the variant genotypes were linked to increased presence of plaque in the carotid, higher atherosclerosis severity score and accelerated ccIMT progression. This tag-SNP has not been widely studied, but one report has regarded it as clinically relevant, after being solidly associated with acute urticaria/angioedema 19 . This polymorphism produces an A-to-T change in the 3′-untranslated (UTR) region of PTGS1 whose functional relevance, however, is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of associations with atherosclerosis measurements revealed that PTGS1 rs10306194, tagging the distal region of the gene coding for COX1, was the most relevant SNP, as the variant genotypes were linked to increased presence of plaque in the carotid, higher atherosclerosis severity score and accelerated ccIMT progression. This tag-SNP has not been widely studied, but one report has regarded it as clinically relevant, after being solidly associated with acute urticaria/angioedema 19 . This polymorphism produces an A-to-T change in the 3′-untranslated (UTR) region of PTGS1 whose functional relevance, however, is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…115 Available data show that NECD and NIUA share similar genetic backgrounds; nevertheless, different gene polymorphisms have been reported. 117,118…”
Section: B I Omark Er S In N Saids Cross -Hyper Sen Sit Ivit Ymentioning
confidence: 99%
“…In NERD, variants in genes associated with LT production (5‐Lipoxygenase, 5‐LOX) and LTC4 synthase and PGs production (COX) pathways were reported 115 . Available data show that NECD and NIUA share similar genetic backgrounds; nevertheless, different gene polymorphisms have been reported 117,118 …”
Section: Biomarkers In Nsaids Cross‐hypersensitivitymentioning
confidence: 99%
“…In addition, CSU patients’ serum can also detect some autoantibodies, such as anti-thyroid peroxidase antibody and anti-cell membrane antibody, and the production of these autoantibodies is also closely related to the inflammatory response [ 9 , 10 ]. For CSU, antihistamines are currently the main treatment method [ 11 ]. However, for some patients, antihistamines may not alleviate their symptoms very well.…”
Section: Introductionmentioning
confidence: 99%